Precision Poultry Farming - Zhao, Yang; Cambra-López, María; De Moura, Daniella Jorge; Zheng, Weichao (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book presents the latest advances in applications of continuous, objective, and automated sensing technologies and computer tools for sustainable and efficient poultry production, and it offers solutions to the poultry industry to address challenges in terms of poultry management, the environment, nutrition, automation and robotics, health, welfare assessment, behavior monitoring, waste management, etc. The reader will find original research papers that address, on a global scale, the sustainability and efficiency of the poultry industry and explore the above-mentioned areas through applications of PPF solutions in poultry meat and egg production